Social movements and the Great Law of Peace in Akwesasne. - Lemelin, Raynald Harvey. (University of Ottawa (Canada), 1997)
Chronicling five different social movements in Akwesasne's contemporary history, this study highlights the progression of changes and reforms associated with concepts and metaphors found in the Kaianerenkowa (Great Law of Peace). Using the theory of Segmentary-Factional-Political Systems this thesis examines how the Kaianerenkowa has been transformed from a lore espounding communal participatory democracy into a socio-political construction serving the needs of various (and sometimes opposing) Mohawk political groups in Akwesasne. In the conclusion we examine the contemporary significance of the Kaianerenkowa in Akwesasne and its possible future role in the community.
Keywords: Anthropology, Cultural.